2018
DOI: 10.17533/udea.penh.v20n2a06
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de edulcorantes no nutritivos: efectos a nivel celular y metabólico

Abstract: ResumenAntecedentes: la función principal de los edulcorantes no nutritivos es proveer al consumidor un producto dulce sin la carga calórica del azúcar. El consumo de edulcorantes no nutritivos se relaciona con alteraciones en el ADN, con apoptosis y con la síntesis de precursores de cáncer. Además, su consumo también se relaciona recientemente con un incremento de tejido adiposo. Objetivo: analizar el efecto de los edulcorantes no nutritivos a largo plazo, evaluando el riesgo de estos compuestos. Materiales y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
1
3
0
1
Order By: Relevance
“…As previous studies have shown, the present study showed that the intake of Stevia sp. (SRN) at a dose of 4.4 g / L does not cause alterations in body weight and can be a compromising alternative to cane sugar or sucrose, however, steviol glycosides in combination with high intensity artificial sweeteners such as sucralose and Isomaltose (SRA) at a dose of 6 g / L, seems not to have the same effects on body weight, showing a trend of increase in body weight more significant than groups C and S, this may be due to the synergy not positive that steviol glycosides could be made in combination with the two artificial sweeteners, in addition, this is consistent with some antecedents that have reported that the intake of non-caloric sweeteners causes a positive body weight compensation due to physiological effects other than those produced due to the caloric consequences, a higher consumption of food after its ingestion, metabolic disorders and the stimulation of taste due to greater consumption of products sweets (Stephens-Camacho et al 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As previous studies have shown, the present study showed that the intake of Stevia sp. (SRN) at a dose of 4.4 g / L does not cause alterations in body weight and can be a compromising alternative to cane sugar or sucrose, however, steviol glycosides in combination with high intensity artificial sweeteners such as sucralose and Isomaltose (SRA) at a dose of 6 g / L, seems not to have the same effects on body weight, showing a trend of increase in body weight more significant than groups C and S, this may be due to the synergy not positive that steviol glycosides could be made in combination with the two artificial sweeteners, in addition, this is consistent with some antecedents that have reported that the intake of non-caloric sweeteners causes a positive body weight compensation due to physiological effects other than those produced due to the caloric consequences, a higher consumption of food after its ingestion, metabolic disorders and the stimulation of taste due to greater consumption of products sweets (Stephens-Camacho et al 2018).…”
Section: Discussionsupporting
confidence: 86%
“…However, when Stevia rebaudiana Bertoni is sold as a sugar substitute, many commercial brands include its steviosides in their formula and combine it with other artificial high-intensity sweeteners (EAI). Although the use of these sweeteners is widespread, their safety as food additives remains controversial, cytotoxic effects and metabolic effects have been reported, casting doubt on whether the consumption of these additives is the most appropriate tool for the control of metabolic diseases (Stephens -Camacho et al 2018). The current results on the use of antioxidants to delay muscle fatigue in humans are contradictory and constitute the main focus of discussion about the role of reactive oxygen species (ROS) in muscle fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding caloric sweeteners, many scientific studies relate the high intake of fructose, glucose, sucrose, honey, and HFCS with diabetes, obesity, metabolic syndrome, hepatic steatosis, nonalcoholic fatty liver, cardiovascular diseases, dental caries, and alterations in the intestinal microbiota [13][14][15][16]. On the other side, regarding noncaloric sweeteners, it has been found that sucralose is related to migraines and insensitivity to insulin, while aspartame is associated with prostate and breast cancer [17,18]. Nevertheless, it is necessary to highlight that research in children on short-and long-term effects has yielded contradictory results [10,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…In two reviews about the use of sweeteners, the results are controversial since some studies have found cytotoxic and metabolic effects, while others have not. Although recognizing that one benefit of sweeteners might be weight loss, the reviews' authors still emphasize the need for longitudinal studies over adequate amounts of time to determine the effects of sweeteners on human health [34,35]. The consumption of sweeteners, commonly found in UPPs, promotes habituation to the sweet taste and this is associated with a higher intake of products with excessive amounts of sugar and, for this reason, they are not recommended for children because of the eating habits that are acquired at an early age [22].…”
Section: Discussionmentioning
confidence: 99%